Black rat Rattus rattus eradication by trapping allows recovery of breeding roseate tern Sterna dougallii and common tern S.hirundo populations on Feno Islet, the Azores, Portugal - Amaral, João J. S. (2017)
Mass trapping successfully achieved elimination of black rat Rattus rattus on Feno islet (1.6 ha), Terceira island (Azores archipelago), thus enabling roseate terns Sterna dougallii and common terns Sterna hirundo to recolonize the islet. Rats were first detected on Feno in 2003, when tern breeding-numbers had decreased dramatically. During 2005 no terns bred on the islet and in 2006 fewer than five common tern pairs attempted to nest. Rat eradication was initiated in September 2006. The last rats were captured in March 2007. Monitoring conducted in September 2007, and May and September 2008 indicated that rats had not recolonized. Common terns quickly resumed breeding on Feno islet but numbers (c.120 pairs in 2009) are still below peak levels (c.240-280 pairs) recorded before rat infestation. Roseate terns on the other hand were slower to return but recovered faster with around 260 pairs in 2009, representing 22% of the Azores population. The success of the black rat eradication shows that surveillance and timely action are fundamental to conserve tern colonies vulnerable to rat predation in the Azores.